2022
DOI: 10.4209/aaqr.210210
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Typhoons on Chemical Makeup of Rainwater in Zhanjiang, China

Abstract: Typhoons are extreme weather events with substantial effects on ambient air. However, whether typhoons of different intensities have the same effects on the chemical composition of rainwater is unclear. Therefore, 4 years of rainwater sampling and an analysis of the ionic composition (Cl − , Ca 2+ , Na + , SO4 2− , Mg 2+ , F − , and K + ) of rainwater were conducted in Zhanjiang, a city on the southern tip of mainland China. The ionic composition varied seasonally, being high in dry seasons and low in wet seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…There are many different ions, such as sodium ions and ammonium ions, in the rainwater of southern China. Among southern cities, such as Chengdu, Chongqing, Shenzhen, Guangzhou, Kunming and Shanghai, the highest sodium ion content was found in the rainwater of Shanghai (Table 2), and coastal cities are proposed to be the major source of sodium ions [31,38,39]. This is comparable to recent foreign studies, where rainwater sodium and ammonium ion levels in Iran were found to be extremely high.…”
Section: Regional Change Of Ph Value In Rainwatersupporting
confidence: 69%
“…There are many different ions, such as sodium ions and ammonium ions, in the rainwater of southern China. Among southern cities, such as Chengdu, Chongqing, Shenzhen, Guangzhou, Kunming and Shanghai, the highest sodium ion content was found in the rainwater of Shanghai (Table 2), and coastal cities are proposed to be the major source of sodium ions [31,38,39]. This is comparable to recent foreign studies, where rainwater sodium and ammonium ion levels in Iran were found to be extremely high.…”
Section: Regional Change Of Ph Value In Rainwatersupporting
confidence: 69%
“…(2017) attributed peak in Cl and Br in a core record from a flooded sinkhole in northern Cuba to increased evaporation associated with regional drying associated with the 8.2 kyr event. Tropical storm systems have also previously demonstrated to be responsible for major depositions of sea salt, of which Cl is a major contributing component to areas further inland (Mullaugh et al., 2013; Sakihama & Tokuyuama, 2005; Zen et al., 2022). Values of this proxy increase from low levels at the base of the core to a major peak in ∼1550, followed by an interval of relatively high levels in the 1570s and another significant peak around 1640.…”
Section: Resultsmentioning
confidence: 99%
“…Both Cl and Br derived from ITRAX have previously been used to assess marine influence over time in coastal lakes (Chagué‐Goff et al., 2016; Oliva, Peros, et al., 2018). In addition, multiple studies have been carried out assessing the importance of major tropical storms delivering Cl derived from surficial ocean waters to the land through rainfall (Mullaugh et al., 2013; Sakihama & Tokuyuama, 2005; Zeng et al., 2022). It has also been determined that the associated rain volume, wind speed, and wind direction significantly influence the concentration of Cl wet deposition in a region (Mullaugh et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The relative flatness of the lake basin and the stability of the body of water favor the formation and preservation of deposition records . This region is located on the coastline of South China and in the tropical convergence zone and the subtropical-tropical transition zone, which is dominated by the East Asian summer monsoon in summer and the East Asian winter monsoon in winter. , The atmospheric deposition of heavy metals from high-latitude West European or North American regions could be transported to middle-latitude East Asian regions through the interaction of the Westerlies with East Asian monsoon. , Thus, the unique location and geography of the lake provide valuable insights into the history of the atmospheric deposition of Pb–Zn and their local and global sources. …”
Section: Methodsmentioning
confidence: 99%